The conundrum of bank capital structure: Empirical evidence from Pakistan - Bilal Sarwar; Muhammad Noor; Nadeem Uz Zaman; Zia Ur Rehman (Cogent Economics & Finance, 2020)
This paper aims to analyze factors explaining the capital structure puzzle in the banking sector of Pakistan. Capital Adequacy Ratio (CAR) is used as a proxy for bank capital structure. Secondary data has been collected from the publications of the State Bank of Pakistan and the annual reports of banks from 2006-2017. The data is analyzed by applying the pooled OLS, fixed effect, and the GMM estimator. The determinants are grouped in (i) bank financial performance (ii) bank risk-based and (iii) industry level. Using bank financial performance indicators, the alternate cost of capital is significant, and management quality is an insignificant determinant of capital structure. Similarly, using bank risk-based variables, default risk, and credit risk is statistically significant whereas, bank risk index is statistically insignificant in explaining capital structure. Furthermore, using the industry-specific variables, both the average CAR of the banking sector and the market competitiveness proxied by the Herfindahl-Hirschman Index (HHI) is significantly predicting capital structure. Overall the bank risk-based and the industry-specific indicators are explaining bank capital structure more significantly compared to other indicators in the study. Finally, this paper included the financial crisis to observe any exogenous shocks while studying capital structure which is found to be significant in the current study.
Keywords: 330; capital adequacy ratio; dynamic panel estimation; generalized method of moments; scheduled commercial banks